Tindak Pidana Pembunuhan Tidak Sengaja Perspektif Hukum Pidana Islam (Analisis Terhadap Konsep Restorative Justice) - Rambe, Ahmad Razaki; Marpaung, Zaid Alfauza (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2024)
This research examines the crime of involuntary manslaughter in the perspective of Islamic criminal law and analyzes it through the concept of restorative justice. In Islamic criminal law, involuntary manslaughter is categorized as murder that occurs without prior intention and plan, where the perpetrator remains responsible even without intent. This analysis uses a normative approach with a descriptive-analytical method, focusing on verses from the Quran, Criminal Code, Prosecutor's Regulations, Police Regulations, hadith, as well as classical and contemporary Islamic legal literature. Restorative justice, as an alternative to the conventional justice system, emphasizes the restoration of relationships between perpetrators and victims, as well as conflict resolution through mediation and reconciliation. In the context of Islamic criminal law, this concept is in line with sharia principles that prioritize peace, restorative justice, and forgiveness. Diyah (fine) and kafarat (atonement) are the main mechanisms in the implementation of restorative justice in accidental murder cases, which aim to compensate the victim's family and restore social balance. This study found that the application of restorative justice in accidental murder cases according to Islamic criminal law is able to provide justice that is more holistic and humanist than the retributive approach. Through a settlement that involves the victim's family and the community, it is hoped that social relations damaged by the criminal offense will be restored.